Aspekte Van Trauma As 'n Gesondheidsprobleem - S. van Tonder (AOSIS, 1979)
Man has been subjected to trauma since the beginning of time. War exposes civilians to greater risks of injury and death than members of the armed forces. In addition to civil defence measures South Africa must increase its ability to handle trauma in peacetime and during any future national emergencies by imposing its educational and research programs in traumatology for public and professional health personnel. Emphasis has been placed by industry on safe equipment and safety methods. The greatest exceptions in this regard are the automobile, density and diversity of traffic, and speed still leads to unprecedented numbers of accidents with many fatalities and disabilities. Lack of adequate control in handling new toxic chemicals as well as handling of household chemicals results annually in many accidental poisonings. Trauma continues to be the leading cause of death for people under the age of 37 years. Its causes are man-made except during natural disasters. It should to a great extent be preventable if we give it the priority and attention it deserves.